PENGELOLAAN AKUNTANSI KEUANGAN, PEMBERDAYAAN SDM DAN MANAJEMEN BUMDes DESA SEMPAN KABUPATEN BANGKA - Abdul Rasyid Saliman; Nana Adriana; Hamdan Hamdan; Afrizal Afrizal; Rita Deseria; Rahmad Firdaus (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
The community service program aims to provide education and guidance to the Management of Village-Owned Enterprises (BUMDes) and relevant community representatives, in order to support the implementation of BUMDes management tasks. This initiative involves a series of training sessions, such as in the fields of financial accounting, human resource empowerment, and management in the village of Sempan, located in the Pemali Subdistrict, Bangka Regency. The establishment of BUMDes is undertaken with a strong intention to realize economic empowerment in the village of Sempan, which holds significant economic potential. BUMDes also carries the responsibility to transparently and accountably compile financial reports for its business units on a monthly basis. However, there are several challenges that need to be addressed, including the lack of collaboration among various relevant parties in the village and a limited understanding of BUMDes management. Through the implementation of this community service program, the outcomes achieved include enhancing the understanding of village officials and BUMDes managers regarding BUMDes governance in Sempan Village, Pemali Sub-district, Bangka Regency. Furthermore, the knowledge and skills of BUMDes managers in financial management and financial reporting are improved. Furthermore, it is anticipated that this community service program will result in an optimal BUMDes management approach, capable of empowering the community, increasing Village Original Income, reducing social disparities, and transforming the village into a more self-reliant entity.